2015
DOI: 10.1038/cddis.2015.165
|View full text |Cite
|
Sign up to set email alerts
|

Sall2 is required for proapoptotic Noxa expression and genotoxic stress-induced apoptosis by doxorubicin

Abstract: The Sall2 transcription factor is deregulated in several cancers; however, little is known about its cellular functions, including its target genes. Recently, we demonstrated that p53 directly regulates Sall2 expression under genotoxic stress. Here, we investigated the role of Sall2 in the context of cellular response to genotoxic stress. In addition, we further examined the Sall2-p53 relationship during genotoxic stress in primary mouse embryo fibroblasts (MEFs), which are derived from Sall2 knockout mice sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 64 publications
1
30
0
Order By: Relevance
“…Sall2 (Sal-like protein 2), a homeotic transcription factor, is commonly considered as a tumor suppressor 41, 42. Cells with deletion of Sall2 ( Sall2 -/- MEFs) showed reduced apoptosis with increased cell viability in response to genotoxic stress 43. Consistent with this report, in our study, we found decreased Sall2 expression in radioresistant cells with reduced cell death in response to radiation and cisplatin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Sall2 (Sal-like protein 2), a homeotic transcription factor, is commonly considered as a tumor suppressor 41, 42. Cells with deletion of Sall2 ( Sall2 -/- MEFs) showed reduced apoptosis with increased cell viability in response to genotoxic stress 43. Consistent with this report, in our study, we found decreased Sall2 expression in radioresistant cells with reduced cell death in response to radiation and cisplatin.…”
Section: Discussionsupporting
confidence: 91%
“…To further investigate the induced function of Sall2, we overexpressed Sall2 and found reversed malignancy of these cancer cells, indicating that Sall2 plays a role in radioresistance. A recent study shows that Sall2 positively regulates Noxa and involves in the apoptotic response to extended genotoxic stress in cancer cells 43. As a transcriptional factor, Sall2 is likely to activate or repress its target genes.…”
Section: Discussionmentioning
confidence: 99%
“…The SV40 large T antigen expression pBSSVD2005 plasmid was a gift from David Ron (Addgene plasmid # 21826), the plasmid containing the CCNE1 promoter was a gift from Bob Weinberg (Addgene plasmid # 8458) (Geng et al ., ), and the CCND1 promoter pGL3Basic was a gift from Frank McCormick (Addgene plasmid # 32726) (McCormick and Tetsu, ). pcDNA3‐SALL2 plasmid was described elsewhere (Escobar et al ., ). Alexa Fluor 488‐conjugated phalloidin and Alexa Fluor 488‐conjugated goat anti‐rabbit secondary antibodies were purchased from Invitrogen (Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 97%
“…Sall2 +/+ and Sall2 −/− fibroblasts were prepared from embryos at 13.5 days postcoitum as previously described (Escobar et al ., ). Briefly, embryos, whose head and other red organs were removed, were smashed into pieces using a razor blade in a 100‐mm dish with 5 mL trypsin (GE Healthcare HyClone, Logan, UT, USA).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation